Characteristics of Hepatobiliary Fascioliasis and the Role of Endoscopic Retrograde Cholangiopancreatography in Management: A Single Center Experience - Bahcecioglu, Ibrahim H.; Tawheed, Ahmed; Tunc, Nurettin; Artas, Hakan; Madkour, Ahmad; Cicek, Sedat; Yalniz, Mehmet (Elsevier - Division Reed Elsevier India Pvt Ltd, 2024)
Background: Hepatobiliary fascioliasis has two phases, each requiring speci fi c management approaches. Triclabendazole has been widely effective in treating the two phases of clinical fascioliasis and endoscopic retrograde cholangiopancreatography (ERCP) in the biliary phase. We aimed to characterize presentations of hepatobiliary fascioliasis and highlight the role of ERCP in management. Subjects and methods: This retrospective cohort includes patients diagnosed with clinical hepatobiliary fascioliasis between January 2013 and December 2022. Demographic data, clinical presentation, laboratory and radiological investigations, treatment, and endoscopy reports were collected from the records of 62 participants. Patients were divided into two groups: acute hepatic and chronic biliary phases. Results: Thirty-six patients were in the biliary phase, and 26 were in the hepatic phase. All patients were from rural areas, and females were predominant (76%). Hypereosinophilia was detected in 92% of acute cases and 58% of chronic biliary cases. In chronic biliary cases, the levels of liver biochemicals, including alanine transaminase (ALT), aspartate aminotransferase (AST), gamma-glutamyltransferase (GGT), and bilirubin, were higher at levels of 189 +/- 76, 127 +/- 47, 268 +/- 77, and 2.4 +/- 0.7 respectively, compared to acute hepatic cases, 35.6 +/- 8.2, 32.7 +/- 4.3, 69.2 +/- 45.45, and 0.58 +/- 0.01. The corresponding P-values were 0.003, 0.001, <0.001, and <0.001, respectively. Triclabendazole effectively cured 93.5% of patients and was used in combination with ERCP in biliary-phase cases where the fl uke was extracted from the biliary system in 34 patients (94.4%). Three patients (8.8%) were diagnosed with post-ERCP pancreatitis. None of the patients experienced bleeding, perforation, or required biliary stenting. Conclusion: Clinical fascioliasis could manifest in acute hepatic or chronic biliary phases. Hypereosinophilia was more evident in the hepatic phases, while ALT, AST, GGT, and bilirubin were higher in the biliary phase. Triclabendazole is effective in the hepatic phase and when combined with ERCP in the biliary phase. ERCP is highly effective for relieving obstruction and treating biliary fascioliasis.
Keywords: fasciola; fascioliasis; ERCP; triclabendazole; eosinophilia; cholestasis; cholangitis